Dynamical systems and cosmology - Coley A A (Dordrecht Kluwer Academic, 2003)
This book provides cosmological models as dynamical systems, with particular emphasis on applications in the early Universe.And also point out the important role of self-similar models and review the asymptotic properties of spatially homogeneous perfect
Keywords: Cosmology; Dynamical systems